2013
DOI: 10.1016/j.biopsych.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Cerebral Cortical Development in Childhood and Adolescence and Adult Attention-Deficit/Hyperactivity Disorder

Abstract: Background Childhood Attention Deficit Hyperactivity Disorder (ADHD) persists into adulthood in around half of those affected (1), constituting a major public health challenge(1). No known demographic, clinical or neuropsychological factors robustly explain clinical course, directing our focus to the brain. Herein, we link the trajectories of cerebral cortical development during childhood and adolescence with the severity of adult ADHD. Methods Using a longitudinal study design, 92 participants with AHD had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
3
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(182 citation statements)
references
References 54 publications
14
158
3
6
Order By: Relevance
“…That the midfrontal theta ERS group difference increased with age (Chabot and Serfontein, 1996;Dickstein et al, 2006; maturational deviation), whereas encoding alpha ERD lagged with age (Kinsbourne, 1973;Mann et al, 1992;Clarke et al, 1998;Rubia, 2007; maturational delay), may further indicate that maintenance impairment emerges from dysfunctional encoding processes. The presence of both developmental trends is consistent with cortical thickness patterns reported by Shaw et al (2007Shaw et al ( , 2010Shaw et al ( , 2013, suggesting that frontal cortex maturity is deviant in ADHD (persisting into adulthood), whereas other regions (including parietal and occipital functions that might subserve encoding alpha) show a maturational delay.…”
Section: Adhd Deficits Of Maintenancesupporting
confidence: 84%
See 1 more Smart Citation
“…That the midfrontal theta ERS group difference increased with age (Chabot and Serfontein, 1996;Dickstein et al, 2006; maturational deviation), whereas encoding alpha ERD lagged with age (Kinsbourne, 1973;Mann et al, 1992;Clarke et al, 1998;Rubia, 2007; maturational delay), may further indicate that maintenance impairment emerges from dysfunctional encoding processes. The presence of both developmental trends is consistent with cortical thickness patterns reported by Shaw et al (2007Shaw et al ( , 2010Shaw et al ( , 2013, suggesting that frontal cortex maturity is deviant in ADHD (persisting into adulthood), whereas other regions (including parietal and occipital functions that might subserve encoding alpha) show a maturational delay.…”
Section: Adhd Deficits Of Maintenancesupporting
confidence: 84%
“…Logistic regression on measures of these processes alone proved able to detect Ïł70% of clinically established ADHD or non-ADHD cases, notable in relation to behavioral rating scales that claim sensitivities of 38 -79% (vs here 69%) and specificities of 13-61% (Snyder et al, 2008;vs here 72%). This finding is encouraging and begs testing of its generalizability in a larger sample, which would also provide sufficient power to test the predictive value of individual measures.…”
Section: Significance To Diagnosis Of Adhdmentioning
confidence: 98%
“…We demonstrate that functional connectivity both within DMN and in DMN interconnections with two task-positive networks (FPN and VAN) is significantly lagged in ADHD. Previous longitudinal investigations of a large cohort of children found maturational lag of structural features of the brain in ADHD (3,(6)(7)(8). Our results demonstrate that there is also maturational lag in the brain's developing functional architecture, and it is relatively specific to connections within DMN and between DMN and TPNs.…”
Section: Discussionsupporting
confidence: 55%
“…One influential neurodevelopmental model of the disorder posits a lag in the maturational trajectories of key features of the brain (1-4). This model has mostly been investigated by examining developmental pathways of structural features of the brain (3,(5)(6)(7)(8). In recent years, however, theorists have increasingly used resting state functional MRI (fMRI)-scanning participants in a task-free resting state-to explore the brain's functional architecture.…”
mentioning
confidence: 99%
“…72 Another study demonstrated that cortical thinning is associated with symptom persistence from childhood into adulthood, and it has been observed that ADHD persistence was greater in girls. 73 The marked difference of ADHD prevalence in childhood seen in clinical samples in itself suggests sex differences, as the ratio of boys to girls with ADHD varies from 3:1 to 9:1. 74 However, the scenario may be different for adult samples from the general popu lation.…”
Section: J Psychiatry Neurosci 2016;41(6)mentioning
confidence: 99%